Scaling Layanan Konsultasi Padi in Indonesia: Key learnings and strategies for nationwide adoption - Bharti, Preeti; Gakhar, Shalini; Subekti, Nuning Argo; Jardinero, Benedict; Pagianti, Tri Selasa; Bugayong, Iris (International Rice Research Institute, 2025)
KEY MESSAGES